Przymus wyborczy a legitymizacja władzy politycznej - Rachwał, Marcin (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2012)
One of the gravest problems of modern democracies is undoubtedly low electoral turnout. Numerous states try to prevent low turnout in different ways. One method to increase it may involve the introduction of compulsory voting, which is a legally regulated prescript to participate in an election. The principal goal of this paper is to attempt to answer the question of whether imposing compulsory voting, and thus obtaining a higher voter turnout, increases the legitimization of representative bodies. The issue of imposing compulsory voting is controversial and does not necessarily have to provide an effective solution to diminishing voter turnout. This is particularly valid for Central and Eastern European states, where imposing an obligation to vote on citizens can be contrary to saving democracy and the legitimization of public authorities. There is a risk that the citizens of countries that found themselves in the orbit of the Soviet Union after WWII may associate compulsory voting with their undemocratic past and as another attack on their rights.